Maternal and neonatal bleeding complications in relation to peripartum management in hemophilia carriers: A systematic review. (September 2021) - Punt, M.C.; Waning, M.L.; Mauser-Bunschoten, E.P.; Kruip, M.J.H.A.; Eikenboom, J.; Nieuwenhuizen, L.; Makelburg, A.B.U.; Driessens, M.H.E.; Duvekot, J.J.; Peters, M.; Middeldorp, J.M.; Bloemenkamp, K.W.M.; et al.
Abstract: Currently, there is no consensus on the optimal management to prevent postpartum hemorrhage (PPH) in hemophilia carriers. We aimed to evaluate peripartum management strategies in relation to maternal and neonatal bleeding outcomes by performing an extensive database search up to August 2020. Seventeen case-reports/series and 11 cohort studies were identified of overall 'poor' quality describing 502 deliveries. The PPH incidence in the individual patient data was 63%; 44% for those women receiving prophylaxis to correct coagulation and 77% for those without (OR 0.23, CI 0.09–0.58) and in cohort data 20.3% (26.8% (11/41) vs. 19.4% (55/284) (OR: 1.53, 95% CI: 0.72–3.24), respectively. Peripartum management strategies mostly consisted of clotting factor concentrates, rarely of desmopressin or plasma. Tranexamic acid appears promising in preventing secondary PPH, but was not used consistently. Neonatal bleeding was described in 6 affected male neonates, mostly after instrumental delivery or emergency CS, but insufficient information was provided to reliably investigate neonatal outcome in relation to management. The high PPH risk seems apparent, at most mildly attenuated by prophylactic treatment. Prospective cohort studies are needed to determine the optimal perinatal management in hemophilia.